The love season - Hilderbrand, Elin. (New York : St. Martin's Press, 2007)
A riveting story that takes place in one day and spans decades; a story that embraces the charming, pristine island of Nantucket, as well as Manhattan, Paris and Morocco.
Includes "Reading group gold" guide.
Keywords: Family secrets -- Fiction; Family secrets; Nantucket Island (Mass.) -- Fiction; Massachusetts -- Nantucket Island; Domestic fiction; Psychological fiction; Domestic fiction; Fiction; Psychological fiction